Leishmanioses: doenças negligenciadas por profissionais da saúde - Carvalho, Richardson Costa (2019)
The increasing number of leishmaniasis cases, the expansion of transmission areas and the high impact on public health show that there are still many challenges to achieving success in the Surveillance and Control Program for this neglected disease. Additionally, the difficulty inherent in early diagnosis and assertive and immediate therapeutic institution, make leishmaniasis still a health problem that plagues society. In 2017, the first cases of human visceral leishmanias is were reported in Lavras, in the south of Minas Gerais state. Since then seven more cases have been reported, two of which died. Regarding the in tegumentary forms, they have also been reported in several municipalities of the region. In this context, it is necessary to study new control strategies, as well as to optimize existing ones to avoid the occurrence of new cases of the disease. Given the above, this study aimed to investigate the cases of VL and LT in the area covered by the Varginha Regional Health Secretariat (SRS) and to know the perception of primary health care professionals (PHC) about this condition. To meet these objectives, the data already existing in Varginha SRS were analyzed, seeking a better understanding regarding the gaps on the theme leishmaniasis. The study included 115 PHC professionals representing all 50 municipalities of the Regional Health. Participants were asked about issues related to the management of leishmaniasis cases, transmission form, clinical signs, biological and epidemiological aspects of the disease. After analysis of the results, it was possible to perceive a lack of knowledge about the local epidemiological reality, difficulties to list prevention and control measures inherent to the reservoir, the environment and the human being. Conceptual gaps may on the part of health professionals reinforce the need for implementation of continuing education programs, since the role of these professionals is essential for the success of the control program.